Empirical Analysis of the Impact of Intellectual Capital on Energy Sector Companies - Afifawati, Nisrina; Khasanah, Lia; Giovanni, Axel (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study examines the phenomenon of intellectual capital in the energy sector and its impact on company value. In the context of the disruptive and VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era, where technological changes and business uncertainties are on the rise, the management of intellectual capital becomes crucial. The aim of this research is to test the influence of intellectual capital on company value in the energy sector. The study employs a quantitative approach, utilizing secondary data from the annual reports of energy sector companies listed on the Indonesia Stock Exchange during the period 2016-2021. The analytical tools used include descriptive statistics and hypothesis testing. The research findings reveal that the disclosure of intellectual capital in the energy sector is considered good, with an average of 13.872%. Statistical analysis indicates a significant influence between intellectual capital and company value, with Tobin’s Q as the company value indicator. This study contributes to understanding the concept of intellectual capital in the context of the energy sector, demonstrating that a larger company value corresponds to higher disclosure of intellectual capital. This conclusion is relevant for managers, investors, and business practitioners dealing with the complexities of the market. The research also establishes a foundation for developing adaptive and responsive strategies to rapid changes in the business environment within the energy sector.